2024
DOI: 10.1002/cbdv.202400206
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, and Insecticidal Activities of Propargyloxy‐Diphenyl Oxide‐Sulfonamide Derivatives

Ziyu Wang,
Tao Guo,
Yu Zhou
et al.

Abstract: Agricultural pests are the primary contributing factor to crop yield reduction, particularly in underdeveloped regions. Despite the significant efficacy of pesticides in pest control, their extensive use has led to the drug‐fast of insecticide resistance. Developing of new environmentally friendly plant‐based pesticides is an urgent necessity. In this study, a series of diaryl ether compounds containing propargyloxy and sulfonamide groups were designed. The synthesis of these 36 compounds primarily relied on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Many neonicotinoid insecticides contain various amine groups, such as imidacloprid, dinotefuran, and thiamethoxam (Figure ). Additionally, it has been reported that the introduction of amine moieties facilitates the enhancement of the insecticidal activity of the lead compounds. , Based on the abovementioned, we proposed to introduce various amine groups on the C-13 position of (+)-nootkatone to enhance its insecticidal activity (Figure ). Herein, we successfully prepared a series of (+)-nootkatone-based amine derivatives using a splicing strategy of active substructures and evaluated their insecticidal activities against three agricultural insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…Many neonicotinoid insecticides contain various amine groups, such as imidacloprid, dinotefuran, and thiamethoxam (Figure ). Additionally, it has been reported that the introduction of amine moieties facilitates the enhancement of the insecticidal activity of the lead compounds. , Based on the abovementioned, we proposed to introduce various amine groups on the C-13 position of (+)-nootkatone to enhance its insecticidal activity (Figure ). Herein, we successfully prepared a series of (+)-nootkatone-based amine derivatives using a splicing strategy of active substructures and evaluated their insecticidal activities against three agricultural insect pests.…”
Section: Introductionmentioning
confidence: 99%